MOLECULAR INVESTIGATION OF HEMOTROPIC MYCOPLASMAS IN HUMAN BEINGS, DOGS AND HORSES IN A RURAL SETTLEMENT IN SOUTHERN BRAZIL - Costa Vieira, Rafael Felipe da; Vidotto, Odilon; Wischral Jayme Vieira, Thallitha Samih; Sa Guimaraes, Ana Marcia; Santos, Andrea Pires dos; Nascimento, Naila Cannes; Rodrigues dos Santos, Nelson Jesse; Martins, Thiago Fernandes; Labruna, Marcelo Bahia; Marcondes, Mary [UNESP]; Biondo, Alexander Welker; Messick, Joanne Belle (Inst Medicina Tropical Sao Paulo, 2015)
The aims of this study were to determine the prevalence of hemoplasmas in a rural Brazilian settlement's population of human beings, their dogs and horses, highly exposed to tick bites; to identify the tick species parasitizing dogs and horses, and analyze factors associated with their infection. Blood samples from 132 dogs, 16 horses and 100 humans were screened using a pan-hemoplasma SYBR green real-time PCR assay followed by a species-specific TaqMan real-time PCR. A total of 59/132 (44.7%) dog samples were positive for hemoplasmas (21 Mycoplasma haemocanis alone, 12 'Candidatus Mycoplasma haematoparvum' alone and 21 both). Only 1/100 (1.0%) human sample was positive by qPCR SYBR green, with no successful amplification of 16S rRNA or 23 rRNA genes despite multiple attempts. All horse samples were negative. Dogs >1 year of age were more likely to be positive for hemoplasmas (p = 0.0014). In conclusion, although canine hemoplasma infection was highly prevalent, cross-species hemoplasma transmission was not observed, and therefore may not frequently occur despite overexposure of agents and vectors.
Keywords: Hemoplasma; Mycoplasma haemocanis; 'Candidatus Mycoplasma haematoparvum'; Real-time PCR